ELEMEN-ELEMEN YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR BARANG KONSUMSI - Purwanti, Purwanti; Sari, Petty Aprilia; Suhariyanto, Suhariyanto (COMPETITIVE, 2023)
This study aims to find out empirically how the elements or factors of intangible assets, company size, funding decisions and profitability on increasing firm value. The presence of company value is very important because it is a good and bad picture of the state of a company and can be considered by potential investors before investing their funds in one company. The better to produce good company value, it is important for companies to explore possible fundamental factors that will have an impact on company value. The population used in this study are manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for the 2015-2019 period. The sampling technique in this study used purposive sampling method. Based on predetermined criteria obtained 9 companies. The method used in analyzing the data is using panel data regression with the help of Eviews version 9 which includes: descriptive statistics, model feasibility test, Chow test, Hausman test, Langrange multiplier test and coefficient of determination. The results of this study indicate that partially intangible assets and profitability have a significant effect on firm value, while firm size, funding decisions have no significant effect on profit growth.